2021
DOI: 10.1111/are.15668
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of marine microalgae used in shrimp hatcheries on Vibrio parahaemolyticus responsible for acute hepatopancreatic necrosis disease

Abstract: Microalgae is used as a source of nutrition for larval and juvenile stages of different species and their use in Aquaculture has increased in the last decades (Oostlander et al., 2020). They provide proteins, lipids, carbohydrates, vitamins, micronutrients and some bioactive compounds. Among the microalgae, genera commonly used in shrimp hatcheries are Chaetoceros, Skeletonema, Thalassiosi ra, Tetraselmis and Isochrysis (Tam et al., 2021). However, it has been recognized that microalgae play a pertinent role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Increased biomass and heightened bioactivity of molecules are commonly observed in co-cultivation approaches. For instance, Chaetoceros calcitrans, a marine diatom, exhibited antimicrobial activity against the pathogenic bacteria Vibrio parahaemolyticus strain MO904 when co-cultured at its logarithmic growth phase [65]. The observed enhancement in bioactivity is believed to stem from the cell-to-cell interactions between the associated microorganisms facilitated by co-cultivation.…”
Section: Recent Status Of Co-cultivation Of Photosynthetic Microorgan...mentioning
confidence: 99%
“…Increased biomass and heightened bioactivity of molecules are commonly observed in co-cultivation approaches. For instance, Chaetoceros calcitrans, a marine diatom, exhibited antimicrobial activity against the pathogenic bacteria Vibrio parahaemolyticus strain MO904 when co-cultured at its logarithmic growth phase [65]. The observed enhancement in bioactivity is believed to stem from the cell-to-cell interactions between the associated microorganisms facilitated by co-cultivation.…”
Section: Recent Status Of Co-cultivation Of Photosynthetic Microorgan...mentioning
confidence: 99%
“…A recent study conducted by Soto-Rodriguez et al (2021) identified that marine microalgae from species Chaetoceros calcitrans possess an antibiotic activity from the hydrophilic compound of its cells towards the highly virulent bacteria Vp M0904 of Vibrio parahaemolyticus strains which are responsible for AHPND or acute hepatopancreatic necrosis disease. Microalgae combination with bacteria such as Isochrysis galbana with Alteromonas sp.…”
Section: Microalgae Application In Aquaculturementioning
confidence: 99%
“…In the aquaculture industry, microalgae have several important roles, including as a source of feed, as bioremediation to utilize aquaculture waste for the photosynthesis process, help reduce excess CO2 levels in waters, and can improve the immune system of aquatic organisms. The results of later studies showed that microalgae have very complex interactions with bacteria, one of which is microalgae can inhibit bacterial growth [1]. Based on this, this study aims to determine the ability of microalgae to anti-vibriosis for disease prevention in shrimp culture.…”
Section: Introductionmentioning
confidence: 99%